Flexural capacity of bi-directional GFRP strengthened RC beams with end anchorages: experimental and theoretical studies - Gora, Abdurra'uf Mukhtar; Jaganathan, Jayaprakash; Anwar, M.P.; Leung, H.Y. (Emerald Publishing, 2018)
This paper presents the results of experimental and theoretical studies on the flexural capacity of reinforced concrete (RC) beams strengthened using externally bonded bi-directional glass fibre reinforced polymer (GFRP) composites and different end anchorage systems. A series of nine RC beams with a length of 1600mm and a cross-section of 200mm depth and 100mm width were prepared and externally strengthened in flexure with bi-directional GFRP composites. These strengthened beams were anchored with three different end anchorage systems namely closed GFRP wraps, GFRP U-wraps, and mechanical anchors. All these beams were tested with four-point bending system up to failure. The experimental results are compared with the theoretical results obtained using the relevant design guidelines. The experimental results demonstrate a significant increase in the flexural performance of the GFRP strengthened beams with regard to the ultimate load carrying capacity and stiffness. The results also show that GFRP strengthened beams without end anchorages experienced intermediate concrete (IC) debonding failure at the GFRP plate end, whereas, all the GFRP Strengthened beams with different end anchorage systems failed in rupture of GFRP with concrete crushing. The theoretical results revealed no significant difference among the relevant design guidelines with regard to the predicted ultimate moment capacities of the bi-directional GFRP strengthened RC beams. However, the results show that ACI Committee 440 (2008) design recommendation provides reasonably acceptable predictions for the ultimate moment capacities of the tested beams strengthened externally with bi-directional GFRP reinforcement followed by FIB Bulletin 14 (2001) and eventually JSCE (1997). The research work presented in this manuscript is authentic and could contribute to the understanding of the overall behaviour of RC beams strengthened with FRP and different end anchorage systems under flexural loading.